Software-defined wireless networking: centralized, distributed, or hybrid? - Abolhasan, Mehran; Lipman, Justin; Wei Ni; Hagelstein, Brett (IEEE network, 2015)
Scalability is a key issue in large scale WDNs, such as vehicular networks and device-to-device networks. To address the issue, this article extends the SDN concept, and presents a new network architecture that eliminates the need of multi-hop flooding for route discovery, thereby enabling WDNs to scale. The key idea of the new architecture is to split network control and data forwarding by using two separate frequency bands. Another important aspect of the architecture is that computational complexity of routing is split between the SDN controller and the forwarding nodes, thereby allowing nodes to make distributed routing decisions. As a result, network control of the new architecture has a hybrid structure, which improves the operability and scalability of large scale WDNs. Our case study shows that the new architecture is able to substantially improve scalability and reliability of WDNs, especially in mobile environments.